Theoretical Foundations for Modelling Bedside Rounds as a Teaching and Practice Activity (II) - Luis Alberto Alberto Corona Martínez; Mercedes Fonseca Hernández (Medisur)
Bedside rounds are the fundamental teaching organizational form of education in the professional practice; it is the backbone of the system of training activities in higher medical education. In this paper, which is a continuation of a previous one, we develop a third idea regarded as essential for modelling bedside rounds: the one related to the formative purpose of such activity. Concrete implications of this idea are specified, complementing the content addressed in the preceding article. Thus, the theoretical framework for the construction of a reference model for the “development” of bedside rounds as a teaching and practice activity is defined.